Determining the needs of the families that have a patient i?n the pediatric intensive care unit and analyzing characteristics of these families - Altay B.; Gonener D.; Zengin N.S.; Ozkaptan B.B. (My University, 2012)
Introduction: In line with the view that accepts the patient and the family as a whole; good care of the families shall be taken throughout the recovery period. Meeting the needs of the family members besides the needs of the pediatric patient will improve the quality of the care in the nursing services. Objective: The study is conducted with the objective of determining the needs of the families that have patients in the pediatric intensive care unit. Material - Method: The universe of this crosssectional study was composed of the families of patients that were in the Pediatric Intensive Care Unit of Samsun Ondokuz Mayıs University Research and Application Hospital on July 01, 2009-November 01, 2009. 200 patient relatives, who will represent 80% of the number of patients that stayed in hospital for the period of three months, were taken into the scope of the study. In data collection, family member description form and Scale for Determining Family Members' Needs were used. In the evaluation of the data, the data were analyzed in SPSS 10.0 package program and t test and variance analysis were conducted with descriptive statistics. Result: When the first 3 important needs that the families who have patients in the intense care unit perceive and score averages were analyzed, being sure that the best care is given to their patients (3.99) takes the first place, receiving honest answers to their questions (3.96) takes the second place and receiving information about the state of the patient at least once a day (3.95) takes the third place. Insufficient notification of family members highlights the points about information need and these needs indicate the anxiety of patients. It was seen that gender, age, degree of relationship and the time spent in the intensive care unit don't affect the need score average of the family members. Moreover, it was determined that the need score averages of the family members are significantly different according to the educational backgrounds and intensive care units (p<0.05). Conclusion: It was determined that seven out of the ten needs perceived as important by family members are information related needs and the remaining three are trust related needs. Intensive care nurses shall know the needs of the families and shall be able to meet them according to the order of priority. Such an approach will support both the patient and family in dealing with the disease.
Keywords: Family; Intensive care; Needs of the family; Pediatric intensive care unit